2021
DOI: 10.1371/journal.pone.0254851
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating iron-loading anemias using a newly developed and analytically validated ELISA for human serum erythroferrone

Abstract: Erythroferrone (ERFE), the erythroid regulator of iron metabolism, inhibits hepcidin to increase iron availability for erythropoiesis. ERFE plays a pathological role during ineffective erythropoiesis as occurs in X-linked sideroblastic anemia (XLSA) and β-thalassemia. Its measurement might serve as an indicator of severity for these diseases. However, for reliable quantification of ERFE analytical characterization is indispensable to determine the assay’s limitations and define proper methodology. We developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
2
3
0
Order By: Relevance
“…The performance of this assay with respect to variability is not yet fully optimised, but even so, for the purpose of this study, circulating levels of ERFE were well-separated in ADHF compared with other diagnoses (4.9 vs. 1.4 ng/ml) allowing good discrimination of ADHF from non-ADHF phenotypes. This is in agreement with other validation studies of human ERFE assays, whereby although certain assay parameters had limitations, pathologies could be differentiated based on ERFE measurement ( 22 ). Second, whilst our sample size is satisfactory for deriving the diagnostic potential for ERFE, it requires validation in a larger, multicentre recruited set of patients with sufficient comorbid cases (e.g., AF, obesity) as well as accurate current iron and/or ferritin measurements.…”
Section: Discussionsupporting
confidence: 92%
“…The performance of this assay with respect to variability is not yet fully optimised, but even so, for the purpose of this study, circulating levels of ERFE were well-separated in ADHF compared with other diagnoses (4.9 vs. 1.4 ng/ml) allowing good discrimination of ADHF from non-ADHF phenotypes. This is in agreement with other validation studies of human ERFE assays, whereby although certain assay parameters had limitations, pathologies could be differentiated based on ERFE measurement ( 22 ). Second, whilst our sample size is satisfactory for deriving the diagnostic potential for ERFE, it requires validation in a larger, multicentre recruited set of patients with sufficient comorbid cases (e.g., AF, obesity) as well as accurate current iron and/or ferritin measurements.…”
Section: Discussionsupporting
confidence: 92%
“…These authors clarify in the abstract poor "dilution linearity" attributed to "presence of a matrix effect and/or different immunoreactivity of the antibodies to the recombinant standard and the endogenous analyte". The partial parallelism plot in Figure 9 is based on the raw data provided in Table 2 in [14]. Consistent with the author's conclusion, this graph convincingly shows absence of parallelism.…”
Section: Examples From the Literaturesupporting
confidence: 82%
“…Lack of parallelism has also been reported explicitly [14]. These authors clarify in the abstract poor "dilution linearity" attributed to "presence of a matrix effect and/or different immunoreactivity of the antibodies to the recombinant standard and the endogenous analyte".…”
Section: Examples From the Literaturementioning
confidence: 80%
See 1 more Smart Citation
“…7 In our previous ERFE-assay validation study, we showed increased ERFE levels in XLSA patients compared to controls. 8 In the current study, we have enriched the ALAS2patient population from our iron expertise centre and included several iron-related parameters to describe the role of the erythropoiesis-hepcidin-iron axis in the pathogenesis of XLSA. Understanding the relationship between this axis and iron loading will help to prevent iron-related toxicity.…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 99%